Comparative Efficacy of Antibiotics and PGF2α in the Treatment of Postpartum Endometritis in Nili-Ravi Buffaloes - Ullah, Abid; Muhammad , Rizwan; Ali, Amjad; Raza, Hafiz Ahsan; Abdul, Qadoos; Nargis , Ambreen; Khan, Imran; Khan, Imran; Khan, Shahzeb; Safiullah; Khan, Imtiaz; Khan, Jahangir; et al. (Indus Journal of Bioscience Research, 2024)
This study compared the effects of ceftiofur HCL, oxytetracycline, and PGF2α on controlling postpartum endometritis and improving reproductive performance in Nili Ravi buffaloes. Sixty-two buffaloes with clinical endometritis were divided into five treatment groups. Group 1 (n=12) received intrauterine oxytetracycline; Group 2 (n=12) received oxytetracycline and PGF2α; Group 3 (n=12) received ceftiofur HCL; Group 4 (n=15) received ceftiofur HCL and PGF2α; and Group 5 (n=11) was the untreated control. Treatment success rates were 75%, 83.33%, 67.33%, 73.33%, and 45.5% in the respective groups. The control group had a significantly lower success rate (P ≤ 0.05). Days to first service were lowest in Group 2 (71.66±16.35). Days open were also significantly lower in Group 2 (106.75±14.66). First and second service conception rates were highest in Group 2 (58.33% and 83.33%). Services per pregnancy were lowest in Group 2 (1.8±0.74). Overall, Group 2 (oxytetracycline + PGF2α) showed better reproductive outcomes compared to the control. The study concluded that oxytetracycline combined with PGF2α improves postpartum reproductive performance in buffaloes.